Virtual Therapy Exergame for Upper Extremity Rehabilitation Using Smart Wearable Sensors - Baron, Lauren; Chheang, Vuthea; Chaudhari, Amit; Liaqat, Arooj; Chandrasekaran, Aishwarya; Wang, Yufan; Cashaback, Joshua; Thostenson, Erik; Barmaki, Roghayeh Leila (IEEE/ACM Conference on Connected Health: Applications, Systems and Engineering Technologies (Online), 2023)
Virtual reality (VR) has been utilized for several applications and has shown great potential for rehabilitation, especially for home therapy. However, these systems solely rely on information from VR hand controllers, which do not fully capture the individual movement of the joints. In this paper, we propose a creative VR therapy exergame for upper extremity rehabilitation using multi-dimensional reaching tasks while simultaneously capturing hand movement from the VR controllers and elbow joint movement from a non-invasive fabric-based wearable sensor made by coating knit fabric with carbon nanotube. We conducted a preliminary study with non-clinical participants (n=12,7\ F) . In a 2× 2 within-subjects study (orientation(vertical, horizontal)× configuration (flat, curved)) , we evaluated the effectiveness and enjoyment of the exergame. The results show that there was a statistically significant difference in terms of task completion time between the two orientations. However, no significant differences were found in the number of mistakes in both orientation and configuration of the virtual exergame. This can lead to customizing therapy while maintaining the same level of intensity. The results of the resistance change generated from the wearable sensor revealed that the flat configuration in the vertical orientation induced more elbow stretches than the other conditions. Finally, we reported the subjective measures based on questionnaires for usability and user experience in different study conditions. In conclusion, the proposed VR exergame has the potential as a multi-modal sensory tool for personalized upper extremity home-based therapy and telerehabilitation.